Current scenario of chalcopyrite bioleaching: A review on the recent advances to its heap-leach technology. (November 2015) - Panda, Sandeep; Akcil, Ata; Pradhan, Nilotpala; Deveci, Haci
Highlights: Current status for bioleaching of chalcopyrite is reviewed. Recent advances in overcoming the problems of passivation have been discussed. Progress made for enhancing chalcopyrite bioleaching is introduced. Emphasis on heap bioleaching plant design and their practical issues is presented. Current practice and aspects related to chalcopyrite heap bioleaching are outlined. Abstract: Chalcopyrite is the primary copper mineral used for production of copper metal. Today, as a result of rapid industrialization, there has been enormous demand to profitably process the low grade chalcopyrite and "dirty" concentrates through bioleaching. In the current scenario, heap bioleaching is the most advanced and preferred eco-friendly technology for processing of low grade, uneconomic/difficult-to-enrich ores for copper extraction. This paper reviews the current status of chalcopyrite bioleaching. Advanced information with the attempts made for understanding the diversity of bioleaching microorganisms; role of OMICs based research for future applications to industrial sectors and chemical/microbial aspects of chalcopyrite bioleaching is discussed. Additionally, the current progress made to overcome the problems of passivation as seen in chalcopyrite bioleaching systems have been conversed. Furthermore, advances in the designing of heap bioleaching plant along with microbial and environmental factors of importance have been reviewed with conclusions into the future prospects of chalcopyrite bioleaching.